Large thrombus-in-transit within a patent foramen ovale in a patient with pulmonary embolism: a case report. Issue 10 (October 2018) - Lu, Changhong; Li, Junfang; Wang, Wugang; Gong, Kun; Zhao, Liang; Fu, Xiuxiu
Objective: A patent foramen ovale (PFO) is detected frequently by echocardiography. However, a thrombus trapped in a PFO is relatively rare. We herein describe a rare case of a 51-year-old patient with pulmonary embolism in which a large thrombus-in-transit through a PFO was found by echocardiography and disappeared after treatment. Methods: A 51-year-old woman presented with a 1-week history of chest tightness, unspecified chest pain, and shortness of breath. Echocardiography revealed a large thrombus trapped in a PFO with increased pulmonary artery pressure, which is a very rare and critical condition. Results: The patient was treated with thrombolysis and anticoagulation and discharged from the hospital with an uneventful recovery. Conclusion: Our treatment of the present patient achieved a satisfactory result, but it may not be applicable to every patient. Echocardiography is a readily available and safe tool for demonstrating the size, location, and extent of a thrombus, and it plays an important role in the early diagnosis and treatment evaluation for patients with a thrombus trapped in a PFO with concurrent pulmonary embolism.